PERBANDINGAN PENGARUH PEMBERIAN KOMPRES HANGAT DAN MINUMAN KUNYIT ASAM DALAM PENURUNAN NYERI HAID (DISMENOREA) PADA REMAJA PUTRI DI KECAMATAN MOJOSONGO - Anggraeni, Titik; Saputro, Bambang Sudono Dwi; Wikanti, Nuraini (Jurnal AKPER GSH, 2021)
Dismenorea rate in Indonesia is 64,25% that consist of primary dismenorea is 54,98% and secondary dismenorea is 9,36%. Primary dismenorea is sufferedby 60 – 75% of the teenagers. Dismenorea causes the woman can’t walk, can’t sleep well, get badmood, lost concentration and the other activities. Disorder one way to decrease dismenorea is by compressing using warm water and consuming turmeric acid. The goal of the research is to knoe the comparison of the influences of compressing using warm water and consuming turmeric acid towrd the decreasing of dismenorea of teenagers in Mojosongo district. This research uses Quasi exsperiment design, with pre and post test with coparation group, where the researcher compares the influences of compressing using warm water and comsuming turmeric acid in this experiment that the samples has benn observed before and after that the sample was reobserved. This research use 30 responndents as the samples by using purposive sampling technique. The data is  processed by using SPSS program to analyze univariate and bivariate with Wilcoxon and Mann Withney U test was got the minimum and maximum score, for warm compress is 0 and 7 and comsuming tumericacid is 0 and 4, with p score is 0,313 so ita can be concluded thereis no significant difference between the group that compressing using warm water and consuming turmeric acid, both of them have influencesfor decreasing disminorea rate.